Preparation method and application of pure copper dendrite etchant
Dental corrosive agent prepared by chemical reagents such as picric acid, stannous chloride, and ferric chloride, solved the problem of displaying morphology of pure copper cast dendrites, and achieved efficient evaluation of cast structure in pure copper casting process. Accurate tissue information is provided to improve casting quality.
Patent Information
- Application Number
- CN202411280714.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The prior art is difficult to show the morphology of pure copper cast dendrites, and there is a lack of effective corrosive agents and methods for evaluating the quality of cast structures in pure copper casting processes.
Dental corrosion agents prepared with chemical reagents such as picric acid, stannous chloride, ferric chloride, hydrochloric acid and anhydrous ethanol are prepared through specific ratios and process steps to prepare pure copper casting billets or ingots for displaying pure copper castings The solidified dendrite structure includes the fine grain structure of the surface, the columnar crystal structure in the middle and the isometric crystal structure in the center.
This method can clearly display the solidified dendrite structure of pure copper casting billets or ingots, improve the quality evaluation efficiency during casting, provide accurate casting structure information, help adjust smelting process parameters, and improve solidification quality during casting process .
Smart Images

Figure CN118777021B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgical analysis, and in particular relates to a preparation method and application of a dendrite corrosive agent for pure copper. Background Art
[0002] The low-magnification inspection methods of sulfur print inspection, hot acid corrosion and electrolytic corrosion have a history of many years. People often use these three methods to carry out low-magnification inspection of mold-cast ingots, billets and steel. Since the continuous casting was put into production, these three methods have also been frequently used in the inspection of continuous casting billets and steel. In order to meet the further needs of production, low-magnification inspection methods of cold acid corrosion and dendrite corrosion have been developed in recent years. Among them, hot acid corrosion, cold acid corrosion and sulfur print inspection can show internal segregation, looseness, cracks and other defects of the billet or ingot, but cannot show the solidified dendrite structure. Dendrite inspection is to mill, grind and polish the sample, and then use a specific corrosion solution to etch or abrade the inspection surface of the sample at room temperature. After a few minutes of corrosion, the solidification structure and defects of the billet can be displayed. Through naked eye observation, combined with scanning photography and magnification observation, the solidification structure and defects of the billet can be accurately judged. Due to its low pollution, high efficiency and the ability to obtain crystalline structure, it has been rapidly promoted and used.
[0003] Crystalline structure refers to the crystallization state reflected on the low-magnification test sample, which is usually composed of three parts: the fine grain structure of the surface, the columnar crystal structure (also known as dendrites) in the middle, and the equiaxed crystal structure in the center. Since there are transition zones of different thicknesses between layers, the boundaries of each layer cannot be distinguished very accurately.
[0004] Dendrite corrosion inspection technology can calculate the equiaxed crystal ratio more accurately, which is difficult to achieve with traditional low-magnification inspection methods. Compared with traditional inspection methods, the dendrite corrosion inspection method can not only clearly display the solidification structure of the continuous casting billet, but also does not expand or shrink. It can accurately display various defects of the original continuous casting billet, providing an important basis for adjusting the smelting production process parameters (such as superheat, roll gap, and reduction), thereby ensuring that the internal quality of the continuous casting billet is effectively controlled.
[0005] However, there is little mention of the dendrite display method of pure copper in existing technologies and researches. Therefore, there is an urgent need to provide an etchant and method for displaying the dendrite morphology of pure copper casting, which can be used for the quality evaluation of the casting structure under the pure copper casting process, so as to achieve the purpose of optimizing and improving the quality of the solidification of the billet or ingot during the casting process. Summary of the invention
[0006] In order to solve the bottleneck problem existing in the above-mentioned prior art, the present invention aims to provide a dendrite etchant for displaying pure copper and a preparation method thereof, which can display the solidified dendrite structure of pure copper billet or ingot, including the fine grain structure of the surface layer, the columnar crystal structure in the middle, and the equiaxed crystal structure in the center. It is used for the quality assessment of the as-cast structure under the pure copper casting process, so as to achieve the purpose of optimizing the solidification of the billet or ingot and improving the quality during the casting process.
[0007] In order to achieve the above-mentioned invention object, the present invention provides a method for preparing a dendrite etchant for pure copper, wherein the dendrite etchant is prepared from picric acid, stannous chloride, ferric chloride, hydrochloric acid, anhydrous ethanol, and distilled water; the volume of the distilled water, the volume of anhydrous ethanol, the volume of hydrochloric acid, the mass of picric acid, the mass of stannous chloride, and the mass of ferric chloride are in the proportion of (50-100) mL: (30-50) mL: (10-30) mL: (1-3) g: (1-3) g: (5-15) g. For example, the mass and volume ratios of various chemical reagents (and their molecular formulas) of 1 portion of the dendrite etchant for pure copper are as follows:
[0008] Picric acid C6H3N3O7, 1~3 g;
[0009] Stannous chloride SnCl2·2H2O, 1~3 g;
[0010] Ferric chloride FeCl3·6H2O, 5~15 g;
[0011] Anhydrous ethanol C2H5OH, 30-50 ml;
[0012] Hydrochloric acid HCl, 10-30 ml;
[0013] Distilled water H2O, 50~100 ml.
[0014] Furthermore, in the above technical solution, the stannous chloride and ferric chloride are both in a crystalline state, and the purity reaches analytical purity or above; the concentration of the hydrochloric acid is 30% to 35%, and the concentration of the hydrochloric acid is preferably 32.3%.
[0015] Distilled water was selected as the solvent, and anhydrous ethanol was added to inhibit corrosion, prevent excessive corrosion, show the microstructure morphology, and affect the observation of dendrite structure. Ferric chloride and picric acid have good corrosion to grain boundaries. The electrode potential of tin ions formed by stannous chloride dissolved in the solvent is higher than that of copper ions, which can promote corrosion and facilitate dendrite display. Chloride ions can reduce the possibility of formation of passivation film on the copper surface or accelerate the destruction of passivation film, promoting local corrosion.
[0016] The preparation method of the pure copper dendrite etchant comprises the following steps:
[0017] ① According to the reagent content requirements, mix distilled water and anhydrous ethanol evenly as the base liquid, add hydrochloric acid to the base liquid and stir evenly;
[0018] ② Add picric acid and stannous chloride to the solution prepared in step ① in sequence and stir evenly;
[0019] ③ Add ferric chloride to the solution prepared in step ②, stir evenly, and ensure that the ferric chloride is completely dissolved in the solution to form a dendrite corrosive agent for pure copper.
[0020] A dendrite etchant for pure copper prepared by the above method.
[0021] An application of the above-mentioned pure copper dendrite etchant, the application process comprises the following steps:
[0022] ① Sample preparation: According to the metallographic observation requirements, grind and polish the test surface of the pure copper sample, and the roughness Ra must be less than 0.8μm, then wash and dry with detergent and hot water above 50℃ for use. Grinding and polishing can be done with a mechanical grinder or a handheld grinder.
[0023] ② Prepare the dendrite etching agent of pure copper according to the above preparation method, and it can be used after being left to stand for more than half an hour.
[0024] ③ When using, use an absorbent cotton ball to dip the corrosive agent and evenly wipe the polished test surface of the sample, and wipe it repeatedly to ensure that no corrosion products are deposited on the test surface until a clear dendrite structure is produced on the test surface.
[0025] ④ Then immediately rinse the test surface with hot water greater than 50°C and blow dry with a hot air blower; then conduct a low-magnification inspection.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] ① It can clearly display the solidified dendrite structure of pure copper billet or ingot, including the fine grain structure on the surface, the columnar crystal structure in the middle, and the equiaxed crystal structure in the center.
[0028] ② Through naked eye observation combined with scanning photography and magnified observation, the solidification structure of the ingot can be accurately judged, which is used to evaluate the quality of the as-cast structure under the pure copper casting process.
[0029] ③This technology has the characteristics of fast inspection speed, high efficiency and easy operation, which solves the problem that the corrosion of pure copper dendrite structure is difficult to show. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a dendrite structure morphology diagram of a pure copper ingot etched by the etchant of the present invention in Example 1;
[0031] Figure 2This is a dendrite structure morphology diagram of a pure copper ingot etched by the etchant of the present invention in Example 2;
[0032] Figure 3 This is a dendrite structure morphology diagram of a pure copper ingot corroded by the corrosive agent of the present invention in Example 3. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific examples, but the present invention is not limited in any way. To avoid redundant description, the raw materials in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.
[0034] A method for preparing a dendrite etchant for pure copper. The dendrite etchant is prepared from picric acid, stannous chloride, ferric chloride, hydrochloric acid, anhydrous ethanol and distilled water. The usage ratio of the volume of the distilled water, the volume of the anhydrous ethanol, the volume of the hydrochloric acid, the mass of the picric acid, the mass of the stannous chloride and the mass of the ferric chloride is (50-100) mL: (30-50) mL: (10-30) mL: (1-3) g: (1-3) g: (5-15) g.
[0035] The matters not described in the following embodiments are the same as the description of the above specific implementation methods.
[0036] Example 1
[0037] A method for preparing a dendrite etchant for pure copper, wherein the dendrite etchant (1 part) is prepared from picric acid, stannous chloride, ferric chloride, anhydrous ethanol, hydrochloric acid, and distilled water; the mass and volume ratios of various chemical reagents (and their molecular formulas) are as follows:
[0038] Picric acid C6H3N3O7, 1.8 g;
[0039] Stannous chloride SnCl2·2H2O, 1.8 g;
[0040] Ferrous chloride FeCl3·6H2O, 7 g;
[0041] Anhydrous ethanol C2H5OH, 40 ml;
[0042] Hydrochloric acid HCl, 15 ml;
[0043] Distilled water H2O, 80 ml.
[0044] The stannous chloride and ferric chloride are both in a crystalline state with analytical purity, and the concentration of the hydrochloric acid is 32.3%.
[0045] The preparation method comprises the following steps:
[0046] ① According to the reagent content requirements, take 80 ml of distilled water and 40 ml of anhydrous ethanol and mix them evenly as the base liquid. Add 15 ml of hydrochloric acid to the base liquid and stir evenly;
[0047] ② Add 1.8 g of picric acid and 1.8 g of stannous chloride to the solution prepared in step ① in sequence and stir evenly;
[0048] ③ Add 7 g of ferric chloride to the solution prepared in step ② and stir evenly to ensure that the ferric chloride is completely dissolved in the solution to form a dendrite corrosive agent for pure copper.
[0049] An application of the above-mentioned pure copper dendrite etchant, the application process comprises the following steps:
[0050] ① Sample preparation: Cut the bottom half section of the pure copper ingot, with a size of about 10 cm square; according to the requirements of metallographic observation, grind the test surface of the pure copper sample with 120#, 400#, and 800# sandpaper respectively, and then polish it with a diamond polishing machine with a particle size of 2.5μm, and the roughness Ra reaches 0.6μm; then wash and dry it with detergent and 55℃ hot water for later use.
[0051] ② According to the above preparation method, prepare a dendrite corrosive agent for pure copper and let it stand for one hour.
[0052] ③ When using, dip the above-mentioned corrosive agent into an absorbent cotton ball and wipe the polished test surface of the sample evenly. Repeat the wiping process for about 2 minutes to ensure that no corrosion products are deposited on the test surface until a clear dendrite structure is formed on the test surface.
[0053] ④ Then immediately rinse the test surface with 55℃ hot water and blow dry with a hot air blower; then conduct a low-magnification test.
[0054] Example 1 The above technical solution was used to test the dendrite structure of pure copper ingots. The test results are as follows: Figure 1 As shown, the dendrite structure of the pure copper sample can be clearly shown, including 1-the fine grain area on the surface, 2-the columnar grain area in the middle, and 3-the equiaxed grain area in the center; and the equiaxed grain rate of the ingot sample can be calculated to be 25%. Obtaining a high proportion of equiaxed grain structure is an effective method to reduce ingot segregation. According to the equiaxed grain rate and the thickness of the dendrite structure, key parameters of the solidification process such as superheat can be adjusted.
[0055] Example 2
[0056] A method for preparing a dendrite etchant for pure copper, wherein the dendrite etchant (1 part) is prepared from picric acid, stannous chloride, ferric chloride, hydrochloric acid, anhydrous ethanol, and distilled water; the mass and volume ratios of various chemical reagents (molecular formulas) are as follows:
[0057] Picric acid C6H3N3O7, 1 g;
[0058] Stannous chloride SnCl2·2H2O, 1 g;
[0059] Ferric chloride FeCl3·6H2O, 5 g;
[0060] Anhydrous ethanol C2H5OH, 30 ml;
[0061] Hydrochloric acid HCl, 10 ml;
[0062] Distilled water H2O, 50 ml.
[0063] The stannous chloride and ferric chloride are both in a crystalline state with analytical purity, and the concentration of the hydrochloric acid is 30%.
[0064] The preparation method comprises the following steps:
[0065] ① According to the reagent content requirements, take 50 ml of distilled water and 30 ml of anhydrous ethanol and mix them evenly as the base liquid. Add 10 ml of hydrochloric acid to the base liquid and stir evenly;
[0066] ②Add 1 g of picric acid and 1 g of stannous chloride to the solution prepared in step ① in sequence and stir evenly;
[0067] ③ Add 5 g of ferric chloride to the solution prepared in step ② and stir evenly to ensure that the ferric chloride is completely dissolved in the solution to form a dendrite corrosive agent for pure copper.
[0068] An application of the above-mentioned pure copper dendrite etchant, the application process comprises the following steps:
[0069] ① Sample preparation: According to the metallographic observation requirements, grind and polish the test surface of the pure copper sample to a roughness Ra of 0.7μm, then wash and dry it with detergent and 60℃ hot water for later use. Grind and polish with a mechanical grinder.
[0070] ② Prepare the dendrite etching agent of pure copper according to the above preparation method, and it can be used only after it has been left to stand for 45 minutes.
[0071] ③ When using, use an absorbent cotton ball to dip the corrosive agent and evenly wipe the polished test surface of the sample, and wipe it repeatedly to ensure that no corrosion products are deposited on the test surface until a clear dendrite structure is produced on the test surface.
[0072] ④ Then immediately rinse the test surface with 60℃ hot water and blow dry with a hot air blower; then conduct a low-magnification test.
[0073] Example 2 The above technical solution was used to test the dendrite structure of pure copper ingots. The test results are as follows: Figure 2As shown, the dendrite structure of the pure copper sample can be clearly shown, including 1-the fine grain area on the surface, 2-the columnar grain area in the middle, and 3-the equiaxed grain area in the center; and the equiaxed grain rate of the ingot sample can be calculated to be 64%. Obtaining a high proportion of equiaxed grain structure is an effective method to reduce ingot segregation. According to the equiaxed grain rate and the thickness of the dendrite structure, key parameters of the solidification process such as superheat can be adjusted.
[0074] Example 3
[0075] A method for preparing a dendrite etchant for pure copper, wherein the dendrite etchant (1 part) is prepared from picric acid, stannous chloride, ferric chloride, hydrochloric acid, anhydrous ethanol, and distilled water; the mass and volume ratios of various chemical reagents (molecular formulas) are as follows:
[0076] Picric acid C6H3N3O7, 3 g;
[0077] Stannous chloride SnCl2·2H2O, 3 g;
[0078] Ferric chloride FeCl3·6H2O, 15 g;
[0079] Anhydrous ethanol C2H5OH, 50 ml;
[0080] Hydrochloric acid HCl, 30 ml;
[0081] Distilled water H2O, 100 ml.
[0082] The stannous chloride and ferric chloride are both in a crystalline state, with a purity higher than analytical grade, and the concentration of the hydrochloric acid is 35%.
[0083] The preparation method comprises the following steps:
[0084] ① According to the reagent content requirements, take 100 ml of distilled water and 50 ml of anhydrous ethanol and mix them evenly as the base liquid. Add 30 ml of hydrochloric acid to the base liquid and stir evenly;
[0085] ② Add 3 g of picric acid and 3 g of stannous chloride to the solution prepared in step ① in sequence and stir evenly;
[0086] ③ Add 15 g of ferric chloride to the solution prepared in step ② and stir evenly to ensure that the ferric chloride is completely dissolved in the solution to form a dendrite corrosive agent for pure copper.
[0087] An application of the above-mentioned pure copper dendrite etchant, the application process comprises the following steps:
[0088] ① Sample preparation: According to the metallographic observation requirements, grind and polish the test surface of the pure copper sample to a roughness Ra of 0.6μm, then wash and dry it with detergent and 60℃ hot water for later use. Grind and polish with a handheld grinder and polisher.
[0089] ② According to the above preparation method, prepare the dendrite etching agent of pure copper, and it can be used after it is left to stand for 1.5 hours.
[0090] ③ When using, use an absorbent cotton ball to dip the corrosive agent and evenly wipe the polished test surface of the sample, and wipe it repeatedly to ensure that no corrosion products are deposited on the test surface until a clear dendrite structure is produced on the test surface.
[0091] ④ Then immediately rinse the test surface with 60℃ hot water and blow dry with a hot air blower; then conduct a low-magnification test.
[0092] Example 3 The above technical solution was used to test the dendrite structure of pure copper ingots. The test results are as follows: Figure 3 As shown, the dendrite structure of the pure copper sample can be clearly shown, including 1-the fine grain area on the surface, 2-the columnar grain area in the middle, and 3-the equiaxed grain area in the center; and the equiaxed grain rate of the ingot sample can be calculated to be 14%. Obtaining a high proportion of equiaxed grain structure is an effective method to reduce ingot segregation. According to the equiaxed grain rate and the thickness of the dendrite structure, key parameters of the solidification process such as superheat can be adjusted.
[0093] Example 4
[0094] A method for preparing a dendrite etchant for pure copper, wherein the dendrite etchant (1 part) is prepared from picric acid, stannous chloride, ferric chloride, hydrochloric acid, anhydrous ethanol, and distilled water; the mass and volume ratios of various chemical reagents (molecular formulas) are as follows:
[0095] Picric acid C6H3N3O7, 1 g;
[0096] Stannous chloride SnCl2·2H2O, 3 g;
[0097] Ferrous chloride FeCl3·6H2O, 8 g;
[0098] Anhydrous ethanol C2H5OH, 45 ml;
[0099] Hydrochloric acid HCl, 20 ml;
[0100] Distilled water H2O, 90 ml.
[0101] The stannous chloride and ferric chloride are both in a crystalline state, with a purity higher than analytical grade, and the concentration of the hydrochloric acid is 35%.
[0102] The preparation method comprises the following steps:
[0103] ① According to the reagent content requirements, take 90 ml of distilled water and 45 ml of anhydrous ethanol and mix them evenly as the base liquid. Add 20 ml of hydrochloric acid to the base liquid and stir evenly;
[0104] ②Add 1 g of picric acid and 3 g of stannous chloride to the solution prepared in step ① in sequence and stir evenly;
[0105] ③ Add 8 g of ferric chloride to the solution prepared in step ② and stir evenly to ensure that the ferric chloride is completely dissolved in the solution to form a dendrite corrosive agent for pure copper.
[0106] An application of the above-mentioned pure copper dendrite etchant, the application process comprises the following steps:
[0107] ① Sample preparation: According to the metallographic observation requirements, grind and polish the test surface of the pure copper sample to a roughness Ra of 0.6μm, then wash and dry it with detergent and 56℃ hot water for later use. Grind and polish with a handheld grinder and polisher.
[0108] ② According to the above preparation method, prepare the dendrite etching agent of pure copper, and it can be used after it is left to stand for 1.4 hours.
[0109] ③ When using, use an absorbent cotton ball to dip the corrosive agent and evenly wipe the polished test surface of the sample, and wipe it repeatedly to ensure that no corrosion products are deposited on the test surface until a clear dendrite structure is produced on the test surface.
[0110] ④ Then immediately rinse the test surface with 56°C hot water and blow dry with a hot air blower; then conduct a low-magnification test.
[0111] Example 4 The above technical solution is used to test the dendrite structure of pure copper ingots, which can clearly show the dendrite structure of the pure copper sample, including 1-fine crystal area on the surface, 2-columnar crystal area in the middle, and 3-equiaxed crystal area in the center; and the equiaxed crystal rate of the ingot sample can be calculated to be 24%. Obtaining a high proportion of equiaxed crystal structure is an effective method to reduce ingot segregation. According to the equiaxed crystal rate and the thickness of the dendrite structure, key parameters of the solidification process such as superheat can be adjusted.
[0112] Example 5
[0113] A method for preparing a dendrite etchant for pure copper, wherein the dendrite etchant (1 part) is prepared from picric acid, stannous chloride, ferric chloride, hydrochloric acid, anhydrous ethanol, and distilled water; the mass and volume ratios of various chemical reagents (molecular formulas) are as follows:
[0114] Picric acid C6H3N3O7, 3 g;
[0115] Stannous chloride SnCl2·2H2O, 1 g;
[0116] Ferric chloride FeCl3·6H2O, 9 g;
[0117] Anhydrous ethanol C2H5OH, 35 ml;
[0118] Hydrochloric acid HCl, 25 ml;
[0119] Distilled water H2O, 70 ml.
[0120] The stannous chloride and ferric chloride are both in a crystalline state, with a purity higher than analytical grade, and the concentration of the hydrochloric acid is 35%.
[0121] The preparation method comprises the following steps:
[0122] ① According to the reagent content requirements, take 70 ml of distilled water and 35 ml of anhydrous ethanol and mix them evenly as the base liquid. Add 25 ml of hydrochloric acid to the base liquid and stir evenly;
[0123] ② Add 3 g of picric acid and 1 g of stannous chloride to the solution prepared in step ① in sequence and stir evenly;
[0124] ③ Add 9 g of ferric chloride to the solution prepared in step ② and stir evenly to ensure that the ferric chloride is completely dissolved in the solution to form a dendrite corrosive agent for pure copper.
[0125] An application of the above-mentioned pure copper dendrite etchant, the application process comprises the following steps:
[0126] ① Sample preparation: According to the metallographic observation requirements, grind and polish the test surface of the pure copper sample to a roughness Ra of 0.6μm, then wash and dry it with detergent and 58℃ hot water for later use. Grind and polish with a handheld grinder and polisher.
[0127] ② According to the above preparation method, prepare the dendrite etching agent of pure copper, and it can be used after it is left to stand for 1.3 hours.
[0128] ③ When using, use an absorbent cotton ball to dip the corrosive agent and evenly wipe the polished test surface of the sample, and wipe it repeatedly to ensure that no corrosion products are deposited on the test surface until a clear dendrite structure is produced on the test surface.
[0129] ④ Then immediately rinse the test surface with 58°C hot water and blow dry with a hot air blower; then conduct a low-magnification test.
[0130] Example 5 The above technical solution is used to test the dendrite structure of pure copper ingots, which can clearly show the dendrite structure of the pure copper sample, including 1-fine crystal area on the surface, 2-columnar crystal area in the middle, and 3-equiaxed crystal area in the center; and the equiaxed crystal rate of the ingot sample can be calculated to be 28%. Obtaining a high proportion of equiaxed crystal structure is an effective method to reduce ingot segregation. According to the equiaxed crystal rate and the thickness of the dendrite structure, key parameters of the solidification process such as superheat can be adjusted.
[0131] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing a pure copper dendrite etchant, characterized in that: The dendrite corrosive agent is prepared from picric acid C6H3N3O7, stannous chloride SnCl2·2H2O, ferric chloride FeCl3·6H2O, hydrochloric acid HCl, anhydrous ethanol C2H5OH and distilled water H2O; the stannous chloride and ferric chloride are in a crystalline state, and the purity reaches analytical purity or above; the concentration of the hydrochloric acid is 30%-35%; the usage ratio of the volume of the distilled water, the volume of the anhydrous ethanol, the volume of the hydrochloric acid, the mass of the picric acid, the mass of the stannous chloride and the mass of the ferric chloride is (50-100) mL: (30-50) mL: (10-30) mL: (1-3) g: (1-3) g: (5-15) g; the preparation method comprises the following steps: ① According to the reagent content requirements, mix distilled water and anhydrous ethanol evenly as the base liquid, add hydrochloric acid to the base liquid and stir evenly; ② Add picric acid and stannous chloride to the solution prepared in step ① in sequence and stir evenly; ③ Add ferric chloride to the solution prepared in step ②, stir evenly, and ensure that the ferric chloride is completely dissolved in the solution to form a dendrite corrosive agent for pure copper.
2. A dendrite etchant for pure copper obtained by the method as claimed in claim 1.
3. An application of the pure copper dendrite etchant as claimed in claim 2, characterized in that: The application process includes the following steps: ① Sample preparation: According to the metallographic observation requirements, grind and polish the test surface of the pure copper sample to a roughness Ra of less than 0.8μm, then wash and dry it with detergent and hot water above 50℃ for later use; ② Prepare the pure copper dendrite etchant according to the above preparation method, and let it stand for more than half an hour before use; ③ When using, use an absorbent cotton ball to dip the corrosive agent and evenly wipe the polished test surface of the sample, and wipe it repeatedly until a clear dendrite structure is produced on the test surface; ④ Then immediately rinse the test surface with hot water greater than 50°C and blow dry with a hot air blower; then analyze and evaluate the solidified dendrite structure.
4. The use of the dendrite etchant for pure copper according to claim 3, characterized in that: The grinding and polishing in step ① are performed using a mechanical grinding and polishing machine.
